The Influence of Service Quality, Customer Trust and Customer Satisfaction on the Customer Loyalty in Cetarip Health Center Patients - Fitriani, Epi; Sudaryo, Yoyo; Mubarok , Dadan Abdul (Dinasti Publisher, 2024)
The purpose of this study was to determine the influence of Service Quality, Customer Trust, and Customer Satisfaction on the Customer Loyalty in Cetarip Health Center Patients both partially and simultaneously. The population in this study were patients at Cetarip Health Center, totaling 100 samples. The sampling technique used in this study was non probability sampling technique. The method used in this research is Quantitative Method with data collection techniques used are interviews and distributing questionnaires to respondents. The data analysis technique used is multiple linear regression with the SPSS program. The results of the study concluded that: (1) service quality have a positive and significant influence on customer loyalty. (2) customer trust has a positive and significant influence on customer loyalty. (3) customer satisfaction has a has a positive and significant influence on customer loyalty. (4) In simultaneous testing, service quality, customer trust, and customer satisfaction have a positive and significant influence on customer loyalty in Cetarip Health Center Patients. The magnitude of the influence of Service Quality, Customer Trust, and Customer Satisfaction is indicated by the Adjusted R Square value of 71,9%% and the remaining 28,1% is influenced by other variables not examined in this study.